The Incidence of HBV and HCV Infection in Australian Travelers to Asia. Issue 3 (12th April 2013) - Johnson, Douglas F.; Ratnam, Irani; Matchett, Elizabeth; Earnest‐Silveria, Linda; Christiansen, Dale; Leder, Karin; Grayson, Michael L.; Torresi, Joseph
Abstract : We analyzed paired pre‐ and post‐travel sera in a cohort of Australian travelers to Asia and demonstrated the acquisition of hepatitis C virus (HCV) and hepatitis B virus (HBV) infection. The incidence density in nonimmune travelers for HCV infection was calculated as 1.8 infections per 10, 000 traveler‐days and for HBV infection 2.19 per 10, 000 traveler‐days.